A new helmeted frog (Anura: Calyptocephalellidae) from an Eocene subtropical lake in northwestern Patagonia, Argentina - Gomez, Raul Orencio (2011)
Eocene caldera-lake deposits from Rio Pichileufu have yielded anuran remains in association with a taxonomically diverse flora. The floral evidence suggests that these anurans lived under climatic conditions similar to those of extant subtropical rainforests. One of the anurans is a helmeted neobatrachian, which is represented by articulated remains and represents a new species that can be assigned to the extant genus Calyptocephalella on the basis of both cranial and postcranial traits. Calyptocephalella pichileufensis, gen. et sp. nov., indicates that, despite the relatively conservative skeletal anatomy of the genus, Calyptocephalella has not always been associated with the temperate austral forests that it inhabits today. The new species also provides evidence of a biotic link with Australia, which has been proposed on the basis of other faunal and floral records, as well as on the paleogeographic history of Patagonia during the mid-Cretaceous-Eocene interval. We also discuss the significance of neobatrachian cranial features that might reflect hyperossification. © 2011 by the Society of Vertebrate Paleontology.